Penegakan Hukum Perhitungan Pengembalian Kerugian Keuangan Negara dalam Tindak Pidana Korupsi - Jiwo, Fadhil; Ajie, Bintang Wicaksono; Amri, Ahmad Almaududy (FOCUS, 2024)
The current developrnent of corruption eradication has focused on three rnain issues, narnely prevention, eradication, and asset recovery. The purpose of the research in this thesis is to find out the ideal construction of regulating the return of state financial losses due to corruption at this tirne and whether it can be irnplernented in the future so that the return of state financial losses due to corruption can create legal certainty. This thesis uses a norrnative legal research rnethod (library) with secondary data and analyzed qualitatively to obtain research results on the ideal construction of regulating the return of state financial losses in corruption crirnes that currently cannot be optirnal as an additional crirne which is part of the purpose of punishing the perpetrators. corruption. Future irnplernentation so that the return of state financial losses due to crirninal acts of corruption requires reconstruction of the provisions in Law Nurnber 31 of 1999 in conjunction with Law Nurnber 20 of 2001 concerning the Eradication of Corruption Crirnes regarding the calculation of state financial losses and the authority of institutions or agencies that calculate financial losses the state in order to create legal certainty in applying additional penalties to perpetrators of corruption.